Brief notes on the destruction of archaeological heritage in central coast valleys during the 21st century - Alvino Loli, Jorge Carlos (2018)
We present some unpublished records about the archaeological heritage that has suffered irreversible damages in the present century in the central coast valleys, between Chancay, Lurín, Chilca and Cañete. The documents are only a random sample of an accelerated process of destruction, often ignored, which is also taking place in many other sites. It is a reflection on the irreparable loss of a series of technological and symbolic kinds of knowledge –which were embodied in spatial distributions, in designs and buildings, and in complex graphic expressions–, which involve the government’s systematic forgetfulness. It has been unable to articulate the temporal and dynamic relationship between ancestral production, communities and the idea of “social development” that resists the rationales of sustainability.